Neighborhood Demographics and the Hazard Resilience of Local Small Businesses - Slovin, Noah (Tufts Archival Research Center, 2020)
This report begins with a literature review that presents the results of similar studies conducted in the past and puts this effort into a larger context. It then presents the methodology, results, and analysis of this study. The discussion section interprets results and proposes a number of explanations for observed trends. The ultimate goal of this report is to contribute to efforts to incorporate social justice and equity concepts into community resilience building by adding the consideration of small businesses resiliency.; Submitted to the Department of Urban and Environmental Policy and Planning.